Aflatoxins in foods (Italian Journal of Public Health, 2007)
Aflatoxins are mycotoxins produced by Aspergillus flavus and A. parasiticus. The aflatoxin group is comprised of aflatoxin B1 (AFB1), B2, G1 and G2. In addition, aflatoxin M1 (AFM1), a hydroxylated metabolite of AFB1, is excreted in the milk of dairy cows consuming an AFB1-contaminated ration. AFB1 has shown extreme acute and chronic toxicity and carcinogenic activity in animals; the acute toxicity of AFM1 is nearly equal to that of AFB1, but its potential carcinogenic hazard is about one order of magnitude less than that of AFB1. The International Agency for Research on Cancer classified AFB1 as a human carcinogen (group 1) and AFM1 as a possible carcinogen (group 2A). Recently, the possibility of a synergistic carcinogenic interaction between HBV chronic infection and dietary exposure to AFB1 arose from the observation of their co-existence in countries with high incidences of HCC and was confirmed by further experimental and epidemiological studies. However, the carcinogenic potency of AFB1 is considered much lower in populations where chronic hepatitis infections are rare. For the first time in 2003, significant problems arose in Italy, due to the aflatoxin contamination of maize. The summer was extremely hot and dry and A. flavus is very competitive under these conditions as the plants are stressed. Maize grain is normally utilized in the food supply for dairy cows and as such led to the severe and widespread contamination of milk with AFM1. In the following years (2004-2006), different climatic conditions as well as better compliance with guidelines by farmers, led to a dramatic reduction of the problem.
Keywords: Aflatoxins; production; toxicity; diffusion; legislation